Renal vasoconstriction is augmented during exercise in patients with peripheral arterial disease. Issue 6 (7th November 2013) - Drew, Rachel C.; Muller, Matthew D.; Blaha, Cheryl A.; Mast, Jessica L.; Heffernan, Matthew J.; Estep, Lauren E.; Cui, Jian; Reed, Amy B.; Sinoway, Lawrence I.
Abstract: Peripheral arterial disease (PAD) patients have augmented blood pressure increases during exercise, heightening their cardiovascular risk. However, it is unknown whether patients have exaggerated renal vasoconstriction during exercise and if oxidative stress contributes to this response. Eleven PAD patients and 10 controls (CON) performed 4‐min mild, rhythmic, plantar flexion exercise of increasing intensity (0.5–2 kg) with each leg (most and least affected in PAD). Eight patients also exercised with their most affected leg during ascorbic acid (AA) infusion. Renal blood flow velocity (RBFV; Doppler ultrasound), mean arterial blood pressure (MAP; Finometer), and heart rate (HR; electrocardiogram [ECG]) were measured. Renal vascular resistance (RVR), an index of renal vasoconstriction, was calculated as MAP/RBFV. Baseline RVR and MAP were similar while HR was higher in PAD than CON (2.08 ± 0.23 vs. 1.87 ± 0.20 au, 94 ± 3 vs. 93 ± 3 mmHg, and 72 ± 3 vs. 59 ± 3 bpm [ P < 0.05] for PAD and CON, respectively). PAD had greater RVR increases during exercise than CON, specifically during the first minute (PAD most: 26 ± 5% and PAD least: 17 ± 5% vs. CON: 3 ± 3%; P < 0.05). AA did not alter baseline RVR, MAP, or HR. AA attenuated the augmented RVR increase in PAD during the first minute of exercise (PAD most: 33 ± 4% vs. PAD most with AA: 21 ± 4%; P < 0.05). In conclusion, these findings suggest that PAD patients have augmented renal vasoconstriction during exercise, with oxidative stress contributing to this response. Abstract : e00154 We investigated renal vascular responses during exercise in patients with peripheral arterial disease (PAD) and healthy controls (CON). Our findings show that renal vasoconstriction is augmented during exercise in PAD patients compared to controls, and can be attenuated with an antioxidant infusion, suggesting that oxidative stress partly contributes to this exaggerated response.